2008
DOI: 10.1074/jbc.m801018200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction between Paramyxovirus Fusion and Attachment Proteins

Abstract: Paramyxovirinae envelope glycoproteins constitute a premier model to dissect how specific and dynamic interactions in multisubunit membrane protein complexes can control deep-seated conformational rearrangements. However, individual residues that determine reciprocal specificity of the viral attachment and fusion (F) proteins have not been identified. We have developed an assay based on a pair of canine distemper virus (CDV) F proteins (strains Onderstepoort (ODP) and Lederle) that share approximately 95% iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
141
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(154 citation statements)
references
References 58 publications
11
141
1
1
Order By: Relevance
“…However, the H protein residues 110 to 114, which are likely to be in close proximity to the F protein in the F-H complex (23), are conserved in all CDV strains. Thus, the attenuation observed for 5804P-H OL may be due in part to the reduced ability of the wild-type F protein to efficiently interact with heterologous H proteins (23). In addition, any of the 60 amino acid differences between the vaccine and wild-type strains may result in conformational changes, thereby subtly altering protein function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the H protein residues 110 to 114, which are likely to be in close proximity to the F protein in the F-H complex (23), are conserved in all CDV strains. Thus, the attenuation observed for 5804P-H OL may be due in part to the reduced ability of the wild-type F protein to efficiently interact with heterologous H proteins (23). In addition, any of the 60 amino acid differences between the vaccine and wild-type strains may result in conformational changes, thereby subtly altering protein function.…”
Section: Discussionmentioning
confidence: 99%
“…However, morbilliviruses recognize proteinaceous receptors (for MeV, the regulator of complement activation [CD46] and/or signaling lymphocytic activation molecule [SLAM], depending on the virus strain) (21,40,46,51,64,65). X-ray data do not extend to the stalk domains, but circular dichroism analysis (78) and structure predictions (36,78) support an ␣-helical coiled-coil configuration of the stalk.…”
mentioning
confidence: 99%
“…The F protein, in type I orientation, forms homotrimers, while homodimers or homotetramers have been suggested as functional units for attachment proteins of different Paramyxovirinae subfamily members (7,14,28,41,49,50,66). For entry, upon receptor binding, the attachment protein is considered to initiate a series of conformational rearrangements in the metastable prefusion F protein (15, 77), which ultimately brings together transmembrane domains and fusion peptides and, thus, donor and target membranes (3,32,45,53,80).Multiple studies have demonstrated that specific interactions between compatible F and attachment proteins of paramyxovirinae are imperative for the formation of functional fusion complexes (6,29,36,42,43,56,75). However, the molecular nature of these interactions and the spatial organization of functional glycoprotein hetero-oligomers remain largely unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently obtained atomic structures of HN stalk domains from NDV HN (12) and PIV5 HN (18) showed the stalks to be four-helix bundles (4HB). A large body of data suggests that F interacts with the attachment protein through the stalk domains (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%